2023
DOI: 10.1080/15592294.2023.2201516
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a bioinformatics approach to predict molecular mechanisms involved in inflammatory response: case of ATRA and 1,25(OH) 2 D in adipocytes

Abstract: Several inflammatory markers such as cytokines, chemokines, and microRNAs (miRNAs) are well known to be induced during obesity and are strongly linked to their comorbidities. Among many others factors, the micronutrient status is suspected to reduce obesity-associated inflammation via blunting inflammatory signalling pathways. This is notably the case for active forms of vitamin A (all-trans retinoic acid ATRA) and vitamin D (1,25(OH) 2 D) as previously shown. In the present study, we ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The activation of the NF-κB signaling pathway was associated with the obesity index, as well as with genomic and epigenetic profiles [ 110 ]. A recent study [ 111 ] combining animal experiments and bioinformatics analyses showed that 1,25(OH) 2 D 3 upregulated 45 mRNAs and putative target miRs and increased the activity of 87 related pathways. Furthermore, bioinformatics analysis revealed that the genes regulated by 1,25(OH) 2 D 3 and their target miRs converged on the classical NF-κB signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the NF-κB signaling pathway was associated with the obesity index, as well as with genomic and epigenetic profiles [ 110 ]. A recent study [ 111 ] combining animal experiments and bioinformatics analyses showed that 1,25(OH) 2 D 3 upregulated 45 mRNAs and putative target miRs and increased the activity of 87 related pathways. Furthermore, bioinformatics analysis revealed that the genes regulated by 1,25(OH) 2 D 3 and their target miRs converged on the classical NF-κB signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown inflammation during obesity or aging-induced miRNA expression, notably in WAT and adipocytes 6 , 8 , 9 , 18 , 20 . Thus, we assessed the expression of an inflammatory miRNA panel in WAT and generated a heatmap with the miRNAs exhibiting statistically significant changes.…”
Section: Discussionmentioning
confidence: 99%
“…This result could be explained by the presence of miR-155 in this cluster, which was involved in inflammatory pathways 6 , 18 . Indeed, studies have demonstrated an upregulation of miR-155 in response to inflammatory stimulations during aging and obesity 20 , 61 . Such induction of miR-155 in our experimental conditions could vigorously participate in adipose tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation